PENGARUH MODEL PEMBELAJARAN TWO STAY TWO STRAY (TSTS) TERHADAP HASIL BELAJAR SISWA - Ana Safitri; Arwin Achmad; Rini Rita T.Marpaung (Universitas Lampung, 2015)
The purpose of this study to determine the effect of using learning the model (TSTS) on students learning outcomes of human reproduction system material at class XI IPA SMAN 1 Sukadana Lampung Timur. The sample was class XI IPA I as experimental class and class XI IPA II as control class by purposive random sampling. The result of TSTS showed student learning outcomes, with an average value of pretest (28,53), posttest (69,6) N-gain (58,28). Class control outcomes had average value of pretest (23,65), posttest (56,99) N-gain (43,72). The increasing of learning result influenced by students learning. In the aspects of asking a question (64%), giving an answer (72%),giving opinion (76%). The result was same in control class. In the aspects of asking a question (57%), giving an answer (58%), and giving an opinion (67%). The conclusion is the using of TSTS learning model have influence towards students learning result and studentslerning activities.Tujuan penelitian untuk mengetahui pengaruh penggunaan model pembelajaran (TSTS) terhadap hasil belajar siswa pada materi pokok sistem reproduksi manusia kelas XI IPA SMAN 1 Sukadana Lampung Timur. Desain penelitian yang digunakan pretest postest kelompok tak ekuivalen sampel penelitian siswa kelas XI IPA1 kelas eksperimen I dan XI IPA2 kelas kontrol dengan teknik purposive sampling. Penggunaan model TSTS menunjukan bahwa rata-rata nilai pretes (28,53), postes (69,6)N-gain (58,28). Sedangkan pada kelas kontrol hasil belajar rata-rata nilai pretes (23,65), postes 56,99, N-gain (43,72). Meningkatnya hasil belajar juga dipengaruhi oleh aktivitas belajar siswa pada aspek bertanya (64%);menjawab pertanyaan (72%);mengungkapkan pendapat (76%). Hasil aktivitas belajar pada kelas control juga berkriteria cukup. Pada aspek bertanya 57% ,menjawab pertanyan 58% mengungkapkan pendapat 67%. Dengan demikian disimpulkan bahwa pengunaan model pembelajaran TSTS berpengaruh terhadap hasil belajar dan aktifitas belajar siswa.Kata kunci : aktivitas belajar, hasil belajar, sistem reproduksi manusia,Two Stay Two Stray